2018
DOI: 10.1017/s0008423917001378
|View full text |Cite
|
Sign up to set email alerts
|

Trust, Economic Development and Attitudes toward Immigration

Abstract: We examine (1) how trust in foreigners and trust in political institutions affect attitudes toward immigration and (2) the moderating effect of economic development on those impacts, analyzing data from the fifth wave of the World Values Survey. We find that natives who trust foreigners are more tolerant toward immigration and that economic development positively moderates the impact of trust in foreigners on the attitudes. Meanwhile, we find only mixed evidence for the impact of trust in political institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In contrast, the rational approach emphasizes the acquired rather than the ascribed aspects, indicating that interpersonal trust depends on the events experienced by individuals during their social life (Uslaner 2008). Individuals learn the specific meanings of cultural and personal traits about trustworthiness through their direct and indirect experiences, and their decisions about whether to trust others are dictated by the outcomes of such experiences (Chang and Kang 2018). If trust can be affected by direct experiences of social interaction, social exclusion can represent a relevant factor in increasing distrustful attitudes.…”
Section: Social Exclusion and Interpersonal Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the rational approach emphasizes the acquired rather than the ascribed aspects, indicating that interpersonal trust depends on the events experienced by individuals during their social life (Uslaner 2008). Individuals learn the specific meanings of cultural and personal traits about trustworthiness through their direct and indirect experiences, and their decisions about whether to trust others are dictated by the outcomes of such experiences (Chang and Kang 2018). If trust can be affected by direct experiences of social interaction, social exclusion can represent a relevant factor in increasing distrustful attitudes.…”
Section: Social Exclusion and Interpersonal Trustmentioning
confidence: 99%
“…Moreover, the role of trust in shaping negative attitudes towards people from different ethnic groups has also been examined (e.g. Chang and Kang 2018;Herreros and Criado 2009;Rustenbach 2010). The authors of these studies found that both abstract (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we consider countries' economic development and individuals' level of education as possible sources of heterogeneous reactions to news on immigration. Some authors (Facchini et al, 2008;Chang and Kang, 2018) find that the native population in more developed countries shows a higher pro-immigrant attitude, triggered by better economic conditions and higher trust in institutions (Chang and Kang, 2018). If this is true, it can be argued that people living in developed countries show a less adverse reaction to news on immigration.…”
Section: Heterogeneity and Robustnessmentioning
confidence: 99%
“…Other studies have reported a statistically significant association between religiosity, religious affiliation, and anti-immigration sentiments (Anderson & Ferguson 2018;Cowling et al 2019;Deslandes & Anderson 2019). Socio-psychological contributors to anti-immigration attitudes include prejudiced stereotypes and misperceptions of immigrants, xenophobia, lack of trust in others (i.e., low social capital), and ethnocentrism (Chang & Kang 2018;Grigorieff et al 2020;Hainmueller & Hangartner 2013;Hjerm 2009). Accounting for these individual beliefs, we use in our estimations indicators for political ideology (1 most liberal to 10 most conservative), religiosity (1 least to 10 most religious), religious affiliations (1 affiliated, 0 unaffiliated), and level of social capital reflecting whether respondents generally trust others (1=yes, 0=no).…”
Section: Samplementioning
confidence: 99%